Indoleamine 2,3-Dioxygenase (IDO) Activity: A Perspective Biomarker for Laboratory Determination in Tumor Immunotherapy - Pengbo Yang; Junhua Zhang (Biomedicines, 2023)
Indoleamine 2,3-dioxygenase 1 (IDO1) is a heme enzyme involved in catalyzing the conversion of tryptophan (Trp) into kynurenine (Kyn) at the first rate-limiting step in the kynurenine pathway of L-tryptophan metabolism. It has been found to be involved in several biological functions such as aging, immune microorganism, neurodegenerative and infectious diseases, and cancer. IDO1 plays an important role in immune tolerance by depleting tryptophan in the tumor microenvironment and inhibiting the proliferation of effector T cells, which makes it an important emerging biomarker for cancer immunotherapy. Therefore, the research and development of IDO1 inhibitors are of great importance for tumor therapy. Of interest, IDO activity assays are of great value in the screening and evaluation of inhibitors. Herein, we mainly review the biological functions of IDO1, immune regulation, key signaling molecules in the response pathway, and the development of IDO1 inhibitors in clinical trials. Furthermore, this review provides a comprehensive overview and, in particular, a discussion of currently available IDO activity assays for use in the evaluation of IDO inhibitors in human blood. We believe that the IDO activity is a promising biomarker for the immune escape and laboratory evaluation of tumor immunotherapy.